Dampak Keberadaan Transportasi Online terhadap Pendapatan UMKM Kuliner di Kota Kendari - Kemal Jusra; Sylsiani Mursalim; Maudhy Satyadharma; Muhammad Yazir Jabbar; Hado Hado; Muhamad Rajulan (Journal of Science, Technology, and Innovation, 2026)
The rapid expansion of digital transportation platforms has transformed the operational landscape of culinary micro, small, and medium enterprises (MSMEs) in urban economies. This study aims to analyze the effect of online transportation services on the income performance of culinary MSMEs in Kendari City within the context of platform-based digital economic transformation. The research employed a quantitative empirical approach using survey data collected from 65 culinary MSME actors integrated with online transportation applications for at least six months. Data were analyzed using validity and reliability testing, simple linear regression, hypothesis testing, and coefficient of determination analysis. The findings reveal that online transportation exerts a positive and statistically significant influence on MSME income, indicated by a regression coefficient of 0.688 and a significance value below 0.05. The coefficient of determination demonstrates that 54.8% of income variation can be explained by the existence of online transportation services. The study also identifies digital adaptation capability, innovation capacity, consumer loyalty, and resilience to platform competition as critical determinants influencing MSME sustainability in the digital economy ecosystem.